Assessment of Growth parameters in Transfusion dependent Thalassemics at a tertiary care hospital - Pattanashetti, Mallikarjun A; Pilli, Ganga S (Annals of Pathology and Laboratory Medicine, 2018)
Background: Thalassemia is a group of genetic blood disorders all of which involve under production of haemoglobin , and partial or complete failure of synthesis a specific type of globin chain . Thalassemia major is most commonÂ monogenic disorder in the world. Around 1,00,000 children are born each year with the severe homozygous state of the disease in India. The objectives of this study was to assess clinical data and the growth parameters of thalassemia major patients attending tertiary care hospital.Beta Thalassemia Major (BTM) is transfusion dependent state where physical growth is affected in majority of patients. This study will emphasize to assess iron overload and growth parameters of transfusion dependent BTM patients. This was undertaken as very few studies have been done in this region of the our country. Methods: The study was done at a tertiary care teaching hospital from January 2014 to December 2014. Universal sampling method was used and 31 Î² thalassemia major patients who receivedÂ blood transfusions at 2 to 4 weeks interval in the hospital were included in this study. Clinical details and blood transfusion record was collected on proforma for all patients and data interpreted. This study was done on 31 known diagnosed BTM patients with age 10 years and above. Height, weight, BMI along with hemoglobin and serum ferritin were estimated. IAP growth charts were plotted for various parameters. Appropriate statistical tests were used for analysis. Result:Â Of 31 patients, 25 were males and 6 were females . Age range was 10 -18 years with mean age of 12.45 years. There were 20(64.5%) patients not taking chelation. Mean and SD of pretransfusion hemoglobin of all patients was 6.85Â±1.13 gm%. Mean and SD of ferritin of all patients, nonchelated and chelatedÂ patients was 3786 Â±2382 ng/ml, 4505Â±2633 ng/ml and 2479 Â± 963.6 ng/ml respectively. Weight for Age (W/A) charts of males and females showed 28% and 16.6 % respectively below 3rd percentile. Height for age (H/A) charts of males showed 40 % below 3rd percentile and none of the females below 3rd percentile. BMI of males and females showed 20% and 50% respectively below 3rd percentile. Most of the patients were of short stature and underweight indicating growth failure. Conclusion: The present study describes the growth parameters of Î² thalassemia major patients attending the tertiary care hospital and emphasizes on maintenance of growth charts ofÂ these patients for better management. Growth failure in BTM is mainly due to iron overload and chronic anemia. This study emphasizes the need of screening for growth failure, regularly estimating iron overload and its control by chelation therapy. DOI:10.21276/APALM.1833